1985
DOI: 10.1111/j.1399-6576.1985.tb02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 13800 Subclavian Vein Catheterizations

Abstract: During the period 1974-1983, 13 857 subclavian or internal jugular vein catheterizations were analysed in the same hospital. The data on the catheterizations have been collected prospectively in the hospital computer. In 93% of the cases, catheterization was subclavian vein cannulation performed through the infraclavicular route. In 15% of the cases the catheter position was not ideal, verified with x-ray; e.g. the catheter tip was turned into the internal jugular vein. Of the catheters 70% were kept in place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
3

Year Published

1988
1988
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 19 publications
2
30
0
3
Order By: Relevance
“…2,3 Central venous cannulation in general is a safe procedure, and complications of the technique are rarely life threatening. 4 However, deaths occur as a direct result of this procedure. 5,6 In this series of 312 patients undergoing percutaneous cannulation, we experienced life-threatening complications in 1.28% of the patients and mortality in 0.32% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Central venous cannulation in general is a safe procedure, and complications of the technique are rarely life threatening. 4 However, deaths occur as a direct result of this procedure. 5,6 In this series of 312 patients undergoing percutaneous cannulation, we experienced life-threatening complications in 1.28% of the patients and mortality in 0.32% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study dealing with 1,500 subclavian venous catheterizations, FELICIANO et al [11] did not describe any cases of AVF. Among the 13,800 cases of subclavian venous catheterizations reported by EEROLA et al [12], there were 113 (0.9%) accidental arterial punctures, but there was no case of an AVF. However, in these two studies, the search for AVF was not systematic, which may explain why no cases were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Trotzdem ist diese Methode nach wie vor mit vielen Komplikationen behaftet. Stellvertretend für die Vielzahl der Berichte über die Häufigkeit der möglichen Komplikationen sei auf die repräsentativen Untersuchungen von Burri [1978] und Eerola et al [ 1985] hingewiesen.…”
Section: Introductionunclassified